Current Preoperative Physiotherapy Management Strategies for Patients Awaiting Anterior Cruciate Ligament Reconstruction (ACLR): A Worldwide Survey of Physiotherapy Practice. Issue 9 (28th September 2020) - Carter, Hayley M.; Webster, Kate E.; Smith, Benjamin E.
Introduction: The optimum time to surgery following ACL rupture remains an outstanding clinical problem. Recent data for the average wait time for an ACLR in the UK is not currently available and anecdotally times range from 4-12 months before an individual undergoes surgery. Globally, the length of time available for preoperative rehabilitation (commonly termed prehabilitation) will vary widely; it is also unknown which subset of patients receive or do not receive prehabilitation and reasons behind this decision making. The current evidence base presents only a small number of RCTs exploring ACL prehabilitation, with inconsistent results on pre- and post-operative outcomes such as muscular strength and function when compared with no prehabilitation. Programmes also vary in content, duration and frequency. Currently, there is no agreed consensus on the best approach to this stage of rehabilitation for this patient group, and thus, current practice is unknown. Hypotheses: This study aimed to explore the current physiotherapy management strategies used during the preoperative phase of rehabilitation for patients awaiting anterior cruciate ligament reconstruction (ACLR). Methods: An anonymous survey was disseminated online via Twitter and the 'interactive Chartered Society of Physiotherapy' message board. Practising physiotherapists who treated at least one patient prior to ACLR in the past year were invited to take part. Responses were collected over a 4-week period in March 2020. Data were analysed using descriptive statistics. Results: In total, 183 respondents replied; 122 completed the full survey. Responses were collected from 20 countries across 3 settings, NHS/public health services, private and sports. Most respondents reported prescribing exercises, advice and education to patients during prehabilitation. Up to 40% also utilised passive treatments including manual therapy, taping/bracing and electrotherapy. The frequency of recommended exercise completion and length of treatment varied. Most respondents (n=103/84.4%) felt that many patients waiting for ACLR did not receive prehabilitation. Many physiotherapists reported that patients expressed concerns regarding their readiness for surgery (n=61/50%) and return to preinjury levels of physical activity (n=112/91.8%). Almost all respondents would discuss non-operative management with patients (n=112/91.8%) if they had returned to their preinjury level of physical activity before their ACLR. Conclusion: Overall, this survey provides some insight as to how physiotherapists manage patients awaiting ACLR. Areas of uncertainty in physiotherapy practice have also been highlighted that require further high-quality research.